The effectiveness and safety of a percutaneous controllable curved plasma radiofrequency ablation device of nucleus pulposus - Hao ZHOU; Qianyi ZHANG; Jiajie LU; Tao WU; Yituo CHEN; Qichen ZHANG; Xilei LI; Haikang CAI; Jie TANG (Zhongguo Linchuang Yixue)
ObjectiveTo verify the safety and effectiveness of a new percutaneous controllable curved plasma radiofrequency instrument for nucleus pulposus ablation. MethodsA new percutaneous controllable curved plasma radiofrequency instrument were designed (controllable curved group), and its ablation effect was compared with the currently used straight head non-bendable plasma ablation instrument (non-bendable group) on gross specimens. The ablation instrument was placed through the right intervertebral foramen, and continuous ablation on the same intervertebral disc was conducted for three times. The ablation range and trajectory were recorded, and the temperature changes in the front, back, left, and right of the ablation center during and 15 seconds after ablation were monitored by the inserted temperature probe. ResultsThere were no difference in temperature changes in the front, back, right regions of the ablation center during and 15 seconds after ablation between the two groups. The temperature changes in the left region of the ablation center both during and 15 seconds after 3rd ablation were larger than those in the non-bendable group (P＜0.01). Compared with the non-bendable group, the controllable curved group achieved angle control and larger single ablation area (2.282 5 mm² vs 1.135 8 mm², P＜0.000 1). ConclusionsThis new percutaneous controllable curved plasma ablation instrument can achieve angle control and ablation on the side opposite to the puncture site, increase ablation volume, and is safe.